2017
DOI: 10.1519/jsc.0000000000001532
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Mixed-Method Cooling Interventions on Preloaded Running Performance in the Heat

Abstract: Stevens, CJ, Bennett, KJM, Sculley, DV, Callister, R, Taylor, L, and Dascombe, BJ. A comparison of mixed-method cooling interventions on preloaded running performance in the heat. J Strength Cond Res 31(3): 620-629, 2017-The purpose of this investigation was to assess the effect of combining practical methods to cool the body on endurance running performance and physiology in the heat. Eleven trained male runners completed 4 randomized, preloaded running time trials (20 minutes at 70% V[Combining Dot Above]O2m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 36 publications
2
53
2
Order By: Relevance
“…Menthol mouth swilling is considered a practical ergogenic strategy before and during exercise in hot environments [11,30] and has been used to improve performance during time trials [17,18] and time to exhaustion [16,31]. Perception of menthol mouth swill concentration may be highly individual in nature, with 200 gene variants of the receptor responsible for menthol detection (TRPM8 [32]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Menthol mouth swilling is considered a practical ergogenic strategy before and during exercise in hot environments [11,30] and has been used to improve performance during time trials [17,18] and time to exhaustion [16,31]. Perception of menthol mouth swill concentration may be highly individual in nature, with 200 gene variants of the receptor responsible for menthol detection (TRPM8 [32]).…”
Section: Discussionmentioning
confidence: 99%
“…All menthol-containing studies [9,10,[16][17][18][19]31] have employed a repeated exposure during the exercise bout-this is quantified via time or distance. Better understanding the time course of menthol mouth swilling responses, and the potential impact of concentrations upon these, would provide insight into possible limitations in application for menthol-containing strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This relative lack of interest in this area may be explained by issues regarding practicality (e.g., excess weight, skin irritation and sport regulations) [104]. Some recent studies suggested that the advantages gained from cooling during exercise may outweigh those of pre-cooling [105,106]. Cooling during exercise is named per-cooling ('per' is derived from the Latin word meaning 'during') [27].…”
Section: Effects Of Cooling During Exercise (Per-cooling)mentioning
confidence: 99%
“…Fewer studies have been conducted examining the effect of a combination of pre and mid-cooling (Stevens et al, 2017). Some studies have demonstrated improved endurance performance using the combination method (Tran Trong et al, 2015) whereas others have reported no benefit (Schultze et al, 2015).…”
Section: Introductionmentioning
confidence: 99%